Harnessing intra-varietal variation for agro-morphological and nutritional traits in a popular rice landrace for sustainable food security in tropical islands - Gautam, Raj Kumar; Singh, Pankaj Kumar; Venkatesan, Kannan; Rakesh, Bandol; Sakthivel, Krishnan; Swain, Sachidananda; Srikumar, Muthulingam; Zamir Ahmed, S. K.; Devakumar, Kishnamoorthy; Rao, Shyam Sunder; Vijayan, Joshitha; Ali, Sharik; et al. (Frontiers in Nutrition, 2023)
Rice crop meets the calorie and nutritional requirements of a larger segment of global population. Here we report the occurrence of intra-varietal variation in a popular rice landrace C14-8 being traditionally grown under geographical isolation of Andaman Islands. Based upon grain husk colour four groups were formed wherein the extent of intra-varietal variation were studied by employing 9 agro-morphological and 13 biochemical traits. Among the traits studied, flavonoid and anthocyanin contents and grain yield exhibited wider spectrum of variability due to more coefficients of variation (>25 %). The first five principal components (PCs) of principal components analysis explained significant proportion of the variation (91 %) and first two PCs explained 63.3 % of the total variation with PC1 and PC2 explaining 35.44 % and 27.91 % respectively. A total of 50 highly variable SSR (HvSSR) markers spanning over 12 chromosomes produced a total of 314 alleles which ranged from one to 15 alleles per marker with an average of 6.28. Of the 314 alleles, 64 were found to be rare among the C14-8 selections. While 62 % HvSSR markers exhibited polymorphism among C14-8 population, chromosomes 2,7,9 and 11 harbored the most polymorphic loci. The group clustering of the selections through HvSSR markers conformed to the grouping based on grain husk coloration. Our studies on existence and pertinence of intra-varietal variations are expected to be of significance in the realms of evolutionary biology and sustainable food and nutritional security under changing climate.